The impact of women’s co-operative in a rural area in achieving Sustainable Development Goals (SDGs) - Rustinsyah Rustinsyah; Pudjio Santoso; Nurul Ratna Sari (Masyarakat, Kebudayaan dan Politik, 2021)
One of the strategies to address the issue of poverty in rural areas is by empowering women. East Java provincial government, Indonesia, has allocated grants for women’s co-operatives in rural areas since 2015, in the same year of the Sustainable Development Goals (SDGs) launch. This study describes the pattern of credit use in the women’s co-operative and its impact on low-income family livelihoods. The research was conducted at two women’s co-operatives in Plumpang District, Tuban Regency, Indonesia, from October 2017 to May 2018 using the qualitative approach. The data were collected through observation, in-depth interviews, focus group discussion, and survey about the co-operative members’ credit use. This study found that the co-operative members used the loans for daily needs, tuition fees, agricultural activities, and non-farming economic activities. The co-operative has increased children’s participation in low-income family informal education and strengthens social capital among poor people in rural areas; however, the co-operative still cannot cut the chain between low-income families and moneylenders the village. Consequently, further development of co-operatives in terms of quality and quantity is necessary for achieving the SDGs.